ANALISIS KONTRAS SPEKEL UNTUK IDENTIFIKASI LILIN PADA BUAH APEL (Mollus domestica) DENGAN METODE LASER SPECKLE IMAGING (LSI) - Wirman, Shabri Putra; Fitrya, Neneng (Sistem Informasi, 2017)
Post-harvest apples are still doing the metabolism process such as respiration and transpiration that lead to decreased fruit quality so that required post-harvest handling, one of them with the waxing process. Wax detection on fruit is difficult to do directly, so further testing is required. One method that can be done is to use optical technology is a speckle imaging system with the LSI (Laser Speckle Imaging) method that is without touching (non-invasive) and without damage (non destructive). The apple contrast value before lamination has a contrast value in the range 0.34637 a.u until 0.38449 a.u. After waxing the apple contrast value decreases. Apples with 4% wax concentration had a contrast value 0.319 a.u, with 6% wax concentration had a contrast value 0.3109 a.u and with 8% wax concentration had a contrast value 0,29895 a.u.